Generation of High-Amylose Rice through CRISPR/Cas9-Mediated Targeted Mutagenesis of Starch Branching Enzymes - Sun, Yongwei; Jiao, Guiai; Liu, Zupei; Zhang, Xin; Li, Jingying; Guo, Xiuping; Du, Wenming; Du, Jinlu; Francis, Frédéric; Zhao, Yunde; Xia, Lanqin (Frontiers in Plant Science, 2017)
ABSTRACT Cereals high in amylose content (AC) and resistant starch (RS) offer potential health benefits. Previous studies using chemical mutagenesis or RNA interference have demonstrated that starch branching enzyme (SBE) plays a major role in determining the fine structure and physical properties of starch. However, it remains a challenge to control starch branching in commercial lines. Here, we use CRISPR/Cas9 technology to generate targeted mutagenesis in SBEI and SBEIIb in rice. The frequencies of obtained homozygous or bi-allelic mutant lines with indels in SBEI and SBEIIb in T0 generation were from 26.7 to 40%. Mutations in the homozygous T0 lines stably transmitted to the T1 generation and those in the bi-allelic lines segregated in a Mendelian fashion. Transgene-free plants carrying only the frame-shifted mutagenesis were recovered in T1 generation following segregation. Whereas no obvious differences were observed between the sbeI mutants and wild type, sbeII mutants showed higher proportion of long chains presented in debranched amylopectin, significantly increased AC and RS content to as higher as 25.0% and 9.8%, respectively, and thus altered fine structure and nutritional properties of starch. Taken together, our results demonstrated for the first time the feasibility to create high-amylose rice through CRISPR/Cas9-mediated editing of SBEIIb.